2005
DOI: 10.1007/s10551-005-8714-9
|View full text |Cite
|
Sign up to set email alerts
|

‘The Impact of Personal and Organizational Moral Philosophies on Marketing Exchange Relationships: A Simulation Using the Prisoner’s Dilemma Game’

Abstract: The purpose of this research is to examine the impact of individual and firm moral philosophies on marketing exchange relationships. Personal moral philosophies range from the extreme forms of true altruists and true egoists, along with three hybrids that represent middle ground (i.e., realistic altruists, tit-for-tats, and realistic egoists). Organizational postures are defined as Ethical Paradigm, Unethical Paradigm, and Neutral Paradigm, which result in changes to personal moral philosophies and company and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Trusting relationships might also control perception of risk and cost of capital. A simulation model of prisoner's dilemma in exchange relationships in a marketing context found consistent results that self-centered firms were outperformed by other-centered sets of firms (Watkins and Hill, 2005).…”
Section: Discussionmentioning
confidence: 81%
“…Trusting relationships might also control perception of risk and cost of capital. A simulation model of prisoner's dilemma in exchange relationships in a marketing context found consistent results that self-centered firms were outperformed by other-centered sets of firms (Watkins and Hill, 2005).…”
Section: Discussionmentioning
confidence: 81%
“…The Effects of Managers' Moral Philosophy resource management (Shultz and Brender-llan, 2004), strategic management (Robertson and Crittenden, 2003), and marketing management (Brinkmann, 2005;Watkins and Hill, 2005). However, little research exists on the relationship between a manager's moral philosophy and a possibly failing project.…”
Section: The Relationship Of Individual Moral Philosophy and Project mentioning
confidence: 99%
“…Using this perspective, organizations as well as individuals seek trustworthy partners who are committed to fair transactions, i.e., dealings that are in the best interest of their firms while also serving the needs of customers (Watkins & Hill, 2005). Research in business ethics has shown the positive impact of developed moral reasoning capability, which provides employees with the skills to navigate such competing demands (Monga, 2007).…”
Section: Orientationmentioning
confidence: 99%